2013
DOI: 10.1038/bjc.2013.741
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of colorectal cancer in BRCA1 and BRCA2 mutation carriers: results from a follow-up study

Abstract: Background: The BRCA1 and BRCA2 genes confer increased susceptibility to breast and ovarian cancer and to a spectrum of other cancers. There is controversy regarding the risk of colorectal cancer conferred by germline mutations in these two genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 16 publications
5
110
0
6
Order By: Relevance
“…Lynch families are characterized by having an excess of synchronous and metachronous colorectal cancer (CRC) but frequently show extra-colonic tumours, including GC [12,13] . Most of Lynch syndrome-associated cancers have h-MLH1, h-MSH2 germline mutations as the causal genetic event underlying MMR deficiency, and only a small fraction of them harbor alterations in h-MSH6 and h-PMS2 genes [14,15] . In addition, loss of MMR system function may also be caused by mechanisms other than germline mutations in MMR genes.…”
Section: Underlying Msi In Gastric Cancermentioning
confidence: 99%
“…Lynch families are characterized by having an excess of synchronous and metachronous colorectal cancer (CRC) but frequently show extra-colonic tumours, including GC [12,13] . Most of Lynch syndrome-associated cancers have h-MLH1, h-MSH2 germline mutations as the causal genetic event underlying MMR deficiency, and only a small fraction of them harbor alterations in h-MSH6 and h-PMS2 genes [14,15] . In addition, loss of MMR system function may also be caused by mechanisms other than germline mutations in MMR genes.…”
Section: Underlying Msi In Gastric Cancermentioning
confidence: 99%
“…However, many of these other studies were based on analysis of confirmed BRCA1 and BRCA2 mutation carriers [6,7,9,[13][14][15]. Because only half of our study population was assumed to have a BRCA mutation, we expected that the cancers associated with BRCA mutations would not have as great an incidence as they would in a population comprised solely of known mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have agreed on a significantly increased risk of pancreatic and prostate cancers in BRCA mutation carriers; however, further information regarding the lifetime risks of these cancers is needed [5,7,13,14]. An increased risk of colon cancer in BRCA mutation carriers has been described, citing relative risks ranging from 0.82 to 4.8 in mutation carriers [15,16]. In 2014, Mersch et al [9] completed a large singleinstitution study of the incidence of non-breast and ovarian cancers in more than 1,000 known BRCA mutation carriers from our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased perception that the broad spectrum of LS cancers can overlap with other hereditary cancer syndromes (21)(22)(23), the use of multiple gene panels can help to elucidate the genetic cause in patients that would have not been diagnosed by using a gene-by-gene limited screening. Somatic NGS panels (15) as well as MSI/IHC testing should also be taken into account in a NGS-based LS-predisposition model (Fig.…”
Section: Are We Ready To Properly Implement Ngs Into the Diagnosticsmentioning
confidence: 99%